If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2y + -6(-3y + 7) = 0 Reorder the terms: 6 + -2y + -6(7 + -3y) = 0 6 + -2y + (7 * -6 + -3y * -6) = 0 6 + -2y + (-42 + 18y) = 0 Reorder the terms: 6 + -42 + -2y + 18y = 0 Combine like terms: 6 + -42 = -36 -36 + -2y + 18y = 0 Combine like terms: -2y + 18y = 16y -36 + 16y = 0 Solving -36 + 16y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 16y = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 16y = 0 + 36 16y = 0 + 36 Combine like terms: 0 + 36 = 36 16y = 36 Divide each side by '16'. y = 2.25 Simplifying y = 2.25
| 7x-8=10+4x | | [3x-2]=10 | | 4w^2+9w=5 | | 7n+5-3n=3(n+2) | | (-6y-9z)(-2)= | | 3x^2-10x-25= | | 4(2c)=11c-33 | | -40+8k=-(k-1)+4 | | 513=825-24x | | 10d-6=4d-3d | | 8t-6(2t-1)= | | 0.10x+15.00=0.15x+10.00 | | -10x+22x= | | 4(x-3)-x=0 | | 82-8x=34 | | H=3st | | 2x+1+12x-4=61 | | [2x+1]=7 | | 3x-6=6x+14 | | 9(3x-1)-26x=2 | | 8x-3+5x-4=79 | | [x]=0 | | 2y-6=7y-26 | | 25-2x=3x+15 | | -10x^2+2x+3=0 | | -3b+4b=-8 | | b/4=13 | | (3m+4)-(2m^2-6m+5)= | | 2x^2=x^4-2x^2 | | (3x-4)=54 | | 3+2+x+2+x+2+3=13.5 | | Z^2-3=54 |